QUALITY MANAGEMENT SYSTEM OF TVER STATE UNIVERSITY - L. N. SKAKOVSKAYA; L. A. KATAUSKAYTE (Высшее образование в России)
The article presents the experience of Tver State University in creating quality management systems (QMS), provides the information on the participation of the University in the procedures of an external independent evaluation of the education quality, the involvement of students in the process of evaluating and improving the quality of educational services of the University. We consider the practical aspects of quality management formation and the formation of the internal system of monitoring and quality assurance, the achievements of TSU to improve the quality management systems.